Mechanical model of the over-stroke displacement behaviour for double concave surface slider anti-seismic devices - Di Cesare, Antonio; Ponzo, Felice Carlo; Telesca, Alessio (Frontiers in Built Environment, 2022)
For Double Concave Curved Surface Sliders (DCCSS) isolators with a flat rim and without restrainers, such as the most commonly used in Europe, the rigid slider could exceed the housing plate geometrical capability in case of earthquakes stronger than the design one. During this over-stroke displacement, the DCCSSs preserve the ability to support gravity loads of superstructure and the capacity of dissipating energy. There are currently no applicable hysteresis rules or available algebraic solutions that can be used to predict the over-stroke behaviour for response-history analysis. This paper presents a algebraic solution to extend basic theories for the estimation of the actual limit displacement of the DCCSS devices with over-stroke capacity. The DCCSS behaviour in the over-stroke sliding regime has been modelled focusing on the geometrical compatibility and kinematics. The proposed analytical formulation has been calibrated on the basis of experimental controlled-displacement tests performed on single DCCSS devices. A case study of a six-storey reinforced concrete frame isolated building has been modelled using a combination of nonlinear elements currently available in several structural analysis software and able to correctly model the over-stroke displacement behaviour for nonlinear time-history analyses. The DCCSS model has been provided with a friction model capable of accounting for torsional effects, axial load and velocity variabilities. The comparison with the nonlinear dynamic analysis outcomes shows that the forces and displacements in the over-stroke sliding regime are predictable and therefore useful for the designer.